Alexithymia and mobile phone addiction in Chinese undergraduate students: The roles of mobile phone use patterns. (August 2019) - Hao, Zejun; Jin, Liangyi; Li, Yan; Akram, Hafiza Rabia; Saeed, Muhammad Farhan; Ma, Jun; Ma, Haibo; Huang, Jinzi
Abstract: Some researchers have pointed out the robust connection between alexithymia and mobile phone addiction. However, few studies have explored, in which way the mobile phone use patterns influenced this relationship. A survey was conducted and 847 Chinese undergraduate students (aged from 18 to 24) joined in this study. Students were tested with questionnaires for measuring their levels of mobile phone addiction, alexithymia and the frequencies of the categorized mobile phone use patterns. Results showed that alexithymia could positively predict mobile phone addiction directly and indirectly via use patterns of entertainment and transaction. Use pattern of interpersonal communication moderated the direct impact of alexithymia on mobile phone addiction. Findings brought new light on the research subject, presenting the relationship between alexithymia and mobile phone addiction and suggested the education authorities the ways of taking good advantage of mobile phones while minimizing their side effects. Highlights: Alexithymia predicts mobile phone addiction. Use patterns of entertainment and transaction partially mediate the relationship. Use pattern of interpersonal communication moderates the direct association.